2016
DOI: 10.4238/gmr.15027259
|View full text |Cite
|
Sign up to set email alerts
|

Roles of microRNA-221/222 in type 2 diabetic patients with post-menopausal breast cancer

Abstract: ABSTRACT. The aim of the research was to examine the expression level of microRNA221/222 (miR-221/222) in the serum of patients with type 2 diabetes mellitus (T2DM) who are also diagnosed with post-menopausal breast cancer. We aimed to evaluate the differences in microRNA expression in patients with T2DM alone, patients with postmenopausal breast cancer alone, and patients with both T2DM and postmenopausal breast cancer. We selected 20 cases from a healthy control group, 30 cases from the group of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
0
13
0
2
Order By: Relevance
“…The main characteristics extracted from various datasets are summarized in Table 1, which includes the number of patients investigated, the measurement platform, type of sample used and the identity of miRNAs in the study [23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81]. Comparing results from multiple tissues provides an overall view of the impact of miRNAs in T2DM pathology.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics extracted from various datasets are summarized in Table 1, which includes the number of patients investigated, the measurement platform, type of sample used and the identity of miRNAs in the study [23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81]. Comparing results from multiple tissues provides an overall view of the impact of miRNAs in T2DM pathology.…”
Section: Resultsmentioning
confidence: 99%
“…14 The pleiotropic role of miR not only gives a selective pressure against their mutations, but it explains the involvement of miRs in several biologic processes. 15 This property is well described for several miRs and might explain the link between diseases co-occurrence. The epigenetic origin of the relationship between obesity and breast cancer (BC) will be investigated in the present paper.…”
Section: Introductionmentioning
confidence: 77%
“…Furthermore, Li et al showed an upregulation in miR-222 serum levels of T2D Chinese women. 38 On the contrary, investigation of miRs expression pattern in the Italian population performed by De Candia et al revealed a decline in miR-222 expression of T2D subjects, which was inversely correlated with glycated hemoglobin and modulated in the plasma samples of diabetic subjects. 39 Inconsistent results concerning miR-15a and miR-222 expressions mentioned in previously performed studies can be attributed to different factors.…”
Section: Discussionmentioning
confidence: 95%